Determinan Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Pekerja PT. X Proyek Pembangunan Tahun 2019 - Rizka Annisa; Hengki Frengki Manullang; Yessi Octavia Simanjuntak (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
International Labor Organization (ILO) 2019, every year 380.000 workers or 13,7 percent of the 2,78 million people die as a result of accidents or occupational diseases, one of the causes is due to the low awareness of employers and employees of the importance of implementing Occupational Health and Safety ( K3), there are around 374 million non-fatal work-related injuries and diseases each year, many of which result in work absences. Compliance is a change in behavior from behavior that does not obey the rules to behavior that obeys the rules. Human behavior is referred to in the